Revealing Multimodal Resources in Teaching-Learning Process for Deaf Students - Fathimah Salma Zahirah; Didi Sukyadi (INKLUSI, 2018)
Deaf students need special treatment for gaining communication skills. Regarding this problem, there has been a new method called Maternal Reflective Method (also known as MRM) that encourages the deaf students to speak using their articulation organs simultaneously with the Indonesian Sign Language. This study aims to discover how nonverbal communication, including touch, body movement, and paralanguage are implemented in a teaching-learning discourse in the kindergarten classroom for the deaf children. The method used by the teacher in delivering the teaching material is the main focus to see the variation of pedagogic multimodal resources. The modes found are also scrutinized due to their communicative implication nature; in regard to Jakobson’s framework on the language functions: referential, emotive, conative, phatic, metalingual, and poetic. The results indicate that most of the time the teacher uses multimodal resources for commanding, prohibiting, and inviting the students in relation to the conative function of language.[Siswa Tuli membutuhkan penanganan khusus dalam mendapatkan kemampuan komunikasi. Berdasarkan hal tersebut, terdapat satu metode bernama Metode Maternal Reflektif (dikenal sebagai MMR) yang mendorong siswa Tuli untuk berbicara menggunakan organ artikulasi bersamaan dengan bahasa isyarat. Penelitian ini bertujuan untuk menelaah bagaimana komunikasi non-verbal, termasuk sentuhan, pergerakan tubuh, dan aspek paralingua diimplementasikan dalam wacana belajar-mengajar di kelas taman kanak-kanak untuk siswa tuli. Metode yang digunakan oleh guru dalam menyampaikan bahan ajar merupakan kunci dalam pencarian variasi sumber daya multimodal pedagogis. Moda-moda yang ditemukan juga diklasifikasikan berdasarkan ciri komunikatifnya; menggunakan teori Jakobson dalam fungsi bahasa: referensial, emotif, konatif, fatis, metalingual, dan puitis. Hasil penelitian mengindikasikan bahwa guru seringkali menggunakan sumber daya multimodal untuk memerintah, melarang, dan mengajak siswa sesuai dengan fungsi konatif bahasa.]